The ending of Armageddon, or the federal principle as the only basis for international peace, liberty and prosperity - Kerr, Philip (Oxford : Alden Press)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: pacifisme; Europese eenmaking